2010
DOI: 10.1037/a0020934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iconicity and semantic relatedness on lexical access in american sign language.

Abstract: Iconicity is a property that pervades the lexicon of many sign languages, including American Sign Language (ASL). Iconic signs exhibit a motivated, non-arbitrary mapping between the form of the sign and its meaning. We investigated whether iconicity enhances semantic priming effects for ASL and whether iconic signs are recognized more quickly than non-iconic signs (controlling for strength of iconicity, semantic relatedness, familiarity, and imageability). Twenty deaf signers made lexical decisions to the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 50 publications
4
52
2
5
Order By: Relevance
“…This view is supported by the fact that structural iconicity has been observed across a wide range of sign language phenomena including the representation of plurals by reduplication (39), of pronouns by using pointing signs toward structured areas of space (8,9,40,41), of agreement markers (9), as well as of metaphors (42,43), and thus may be a general property of signing systems. Moreover, the precise nature of the mapping biases that sign languages appear to use suggests an iconic and nonarbitrary mapping between telic structure and visual structure.…”
Section: Discussionmentioning
confidence: 95%
“…This view is supported by the fact that structural iconicity has been observed across a wide range of sign language phenomena including the representation of plurals by reduplication (39), of pronouns by using pointing signs toward structured areas of space (8,9,40,41), of agreement markers (9), as well as of metaphors (42,43), and thus may be a general property of signing systems. Moreover, the precise nature of the mapping biases that sign languages appear to use suggests an iconic and nonarbitrary mapping between telic structure and visual structure.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to Thompson et al [21], Bosworth & Emmorey [22] found no effect of iconicity on sign recognition, as assessed by lexical decision (i.e. decide whether a given form is an existing sign).…”
Section: Structure-mapping Theory and Iconicitymentioning
confidence: 77%
“…However, for the target sign BOOK, the structural correspondences involve the properties of an object: the hands correspond to the halves of a book when opened. A post hoc analysis by Bosworth & Emmorey [22] suggested that a general similarity in the type of structural overlap was not enough to increase priming. That is, prime -target pairs with a generally similar mapping (e.g.…”
Section: Structure-mapping Theory and Iconicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of iconicity in processing the language and lexical access is under debate (Bosworth & Emmorey, 2010), and it is thus important to be able to control for this when selecting experimental stimuli. However, iconicity is not a simple binary property, and the relation between the form and the meaning of a sign may be of several different types (Taub, 2001).…”
Section: Type Of Sign and Iconicitymentioning
confidence: 99%